Fahrenheit 11/9 [videorecording (DVD)] - Moore, Michael, 1954 April 23-; Moore, Michael, 1954 April 23-; Hogg, David, 2000-; Trump, Donald, 1946- (State Run Films, 2018)
Filmmaker Michael Moore examines the current state of American politics, particularly the Donald Trump presidency and gun violence, while highlighting the power of grassroots democratic movements. --